Neuroendocrine Tumor Diagnosed Through Endoscopic Ultrasound-Guided Fine-Needle Biopsy of a Lung Mass. Issue 9 (1st September 2022) - Abdallah, Mohamed; McDonald, Nicholas; Hanson, Brian; Suryawanshi, Gaurav; Bilal, Mohammad
ABSTRACT: Endoscopic ultrasound-guided fine-needle biopsy (EUS-FNB) is an excellent modality for tissue acquisition and has been shown to be superior to EUS-fine-needle aspiration in several studies. Although tissue sampling of lung nodules using EUS-fine-needle aspiration has been reported in the literature, the use of EUS-FNB for tissue acquisition of parenchymal lung mass has rarely been reported in the literature. Our report highlights that EUS-FNB is safe and effective for lung lesions that are near the esophageal wall.